Healthcare providers' knowledge, attitude, and practice on quality of nutrition care in hospitals from a developing country: a multicenter experience - Muna Shakhshir; Abdulsalam Alkaiyat (BMC, 2023)
Abstract Background Despite the fact that malnutrition can affect both recovery and outcome in acute care patients, little is known about malnutrition in Palestine, and even less is known about the assessment of malnutrition knowledge, attitudes, and practices (M-KAP) toward healthcare providers and nutrition care quality measures in hospitalized patients. Therefore, this study aimed to evaluate the M-KAP of physicians and nurses in routine clinical care and determine the influencing factors. Methods From April 1 to June 31, 2019, cross-sectional research was performed at governmental (n = 5) and non-governmental (n = 4) hospitals in the North West Bank of Palestine. Data were collected using a structured self-administered questionnaire from physicians and nurses to collect information on knowledge, attitude, and practices related to malnutrition and nutrition care, alongside sociodemographic characteristics. Results A total of 405 physicians and nurses were participated in the study. Only 56% of participants strongly agreed that nutrition was important, only 27% strongly agreed that there should be nutrition screening, only 25% felt food helped with recovery, and around 12% felt nutrition as part of their job. Approximately 70% of participants said they should refer to a dietitian, but only 23% knew how and only 13% knew when. The median knowledge/attitude score was 71, with an IQR ranging from 65.00 to 75.00, and the median practice score was 15.00 with an IQR of 13.00-18.00. The mean knowledge attitude practice score was 85.62 out of 128 with SD (9.50). Respondents who worked in non-governmental hospitals showed higher practice scores (p < 0.05), while staff nurses and ICU workers showed the highest practice score (p < 0.001). Respondents with younger age categories, working in non-governmental hospitals in the ICU as practical and staff nurses, showed the highest KAP score (p < 0.05). Significance positive correlations were found between respondents' knowledge/attitude and practice scores regarding the quality of nutrition care in hospitals (r = 0.384, p value < 0.05). In addition, the result also revealed that almost half of respondents believed that the most important barriers to inadequate intake of food at the bedside are related to food appearance, taste, and aroma of meals served (58.0%). Conclusions The research revealed that inadequate knowledge was perceived as a barrier to effective nutrition care to the patient. Many beliefs and attitudes do not always translate into practice. Although the M-KAP of physicians and nurses is lower than in some other countries/studies, it highlights a strong need for more nutrition professionals in the hospital and increasing nutrition education to improve nutrition care in hospitals in Palestine. Furthermore, establishing a nutrition task force in hospitals elaborated by dietitians as the unique nutrition care provider will assure to implementation of a standardized nutrition care process.